1992
DOI: 10.1111/j.1432-1033.1992.tb17298.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and paritial characterization of a thermostable trithionate hydrolase from the acidophilic sulphur oxidizer Thiobacillus acidophilus

Abstract: Ccll-free extracts of Thiobacillus acidophilus catalysed the quantitative conversion of trithionate (S,Oz -) to thiosulphate and sulphate. A continuous assay for quantification of experimental results was based on the difference in absorbance between trithionate and thiosulphate at 220 nm.Trithionate hydrolase was purified to near homogeneity from cell-free extracts of T . acidophilus. The molecular masses of the native enzyme and the subunit were 99 kDa (gel filtration) and 34 kDa (SDS/PAGE). The purified enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…This is an unusual enzymatic reaction that has only otherwise been suggested for enzymes designated as trithionate or tetrathionate hydrolases (15)(16)(17)(18). The thiosulfohydrolase activity proposed for SoxB has yet to be directly demonstrated.…”
Section: Soxy-shmentioning
confidence: 99%
“…This is an unusual enzymatic reaction that has only otherwise been suggested for enzymes designated as trithionate or tetrathionate hydrolases (15)(16)(17)(18). The thiosulfohydrolase activity proposed for SoxB has yet to be directly demonstrated.…”
Section: Soxy-shmentioning
confidence: 99%
“…Further studies such as X-ray crystallography of the purified protein may resolve the reason behind the heat tolerance. Similar studies of thermostable enzymes of mesophilic bacteria have been conducted for trithionate hydrolase of Acidithiobacillus acidophilus and sulfur oxygenase reductase of Halothiobacillus neapolitanus (Meulenberg et al, 1992;Veith et al, 2012).…”
mentioning
confidence: 59%
“…This result suggested that the SCNase may have a special property of cold inactivation and heat reactivation. The characteristic of cold inactivation was also found in other enzymes such as E. coli tryptophanase (Erez et al, 1998), trithionate hydrolase of Thiobacillus acidophilus (reclassified as Acidiphilium acidophilum) (Meulenberg et al, 1992) and ribulose-1,5-biphosphate carboxylase-oxygenase from tobacco leaf (Chollet & Anderson, 1977). In the latter, the cold inactivation was the result of partial dissociation of the hydrophobic catalytic subunits of the enzyme (Chollet & Anderson, 1977).…”
mentioning
confidence: 79%
“…The thiosulfateoxidizing enzyme was successfully solubilized from intact cells by passing the acidic ammonium sulfate suspension through a French pressure cell following the procedures for trithionate hydrolase isolation from Thiobacillus acidophilus (Meulenberg et al 1992), although this latter enzyme activity was not found in our sulfur-grown T. thiooxidans. 2.…”
Section: Thiosulfate Oxidation By the Acidic Extractmentioning
confidence: 99%